Changes in the Distribution Preference of Soil Microbial Communities During Secondary Succession in a Temperate Mountain Forest - Li, Peikun; Zhang, Jian; Wang, Senlin; Zhang, Panpan; Chen, Wenju; Ding, Shengyan; Xi, Jingjing (Frontiers in Microbiology, 2022)
Soil microbes play a crucial role in a forest ecosystem. However, whether the distribution of bacteria and fungi in different forest succession stages is random or following ecological specialization remains to be further studied. In the present study, we characterized soil bacterial and fungal communities to determine their distribution preference, with different succession communities in a temperate mountain forest. The Kruskal–Wallis method was used to analyze structural differences between bacterial and fungal communities in different succession processes. The specificity of soil microbial distribution in a secondary forest was studied by network analysis. The torus-translation test was used to analyze the species distribution preference of soil microbes in different succession stages. Results showed that the species composition of soil bacteria and fungi differed significantly in different succession processes. The modularity index of fungi (0.227) was higher than that of bacteria (0.080). Fungi (54.47%) had specific preferences than bacteria (49.95%) with regard to forests in different succession stages. Our work suggests that the distribution pattern of most soil microbes in a temperate mountain forest was not random but specialized in temperate mountain forests. Different microbes showed different distribution preferences. Fungi were more sensitive than bacteria during secondary succession in a temperate mountain forest. In addition, microbe–environment relations varied during secondary succession. Our results provided new insight into the mechanism through which complex soil microbial communities responded to changes in forest community succession.